2001
DOI: 10.1089/152308601317203567
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effects of Resveratrol

Abstract: Resveratrol (3,4',5-trihydroxy-trans-stilbene) is a common phytoalexin that is found in a few edible materials, such as grape skins, peanuts, and red wine. It has been speculated that dietary resveratrol may act as an antioxidant, promote nitric oxide production, inhibit platelet aggregation, and increase high-density lipoprotein cholesterol, and thereby serve as a cardioprotective agent. Based on epidemiological data, carcinogenesis and coronary heart disease are linked to dietary lifestyle and share a number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
263
1
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 446 publications
(280 citation statements)
references
References 121 publications
5
263
1
11
Order By: Relevance
“…The positive effects of resveratrol in biological systems are wide-ranging. It acts as a cancer chemoprevention agent [16], a powerful anti-inflammatory factor and an antioxidant agent [17,18]. Its cardiovascular properties, including inhibition of platelet aggregation and promotion of vasodilation by enhancing the production of NO [19] have also been described [15,20] and recent studies have reported its beneficial effects against ageing and metabolic diseases [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The positive effects of resveratrol in biological systems are wide-ranging. It acts as a cancer chemoprevention agent [16], a powerful anti-inflammatory factor and an antioxidant agent [17,18]. Its cardiovascular properties, including inhibition of platelet aggregation and promotion of vasodilation by enhancing the production of NO [19] have also been described [15,20] and recent studies have reported its beneficial effects against ageing and metabolic diseases [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological research has revealed a link between the consumption of red wine, an important source of resveratrol, and reduced risk of cardiovascular disease in France. Consequently, resveratrol has been extensively studied, and numerous beneficial effects have been observed, including antithrombotic, cardioprotective, anti-inflammatory, antioxidative, and vasorelaxant effects (Bhat et al, 2001;Delmas et al, 2005;KasdallahGrissa et al, 2007;Stef et al, 2006;). In addition, resveratrol exhibits antitumor properties in several cancer types, including prostate, mammary, colon, and lung cancers (Bhat and Pezzuto, 2002;Revel et al, 2003;Schneider et al, 2000;Stewart et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol (3,4 0 ,5-trihydroxy-trans-stilbene), a polyphenolic phytoalexin found in the skin of red grapes and a variety of other fruits, functions in plants to protect against fungal infections (5). A variety of studies have reported that resveratrol has cardioprotective, antioxidant, anti-inflammatory, antibacterial, and antiviral activities (6). In addition, resveratrol was found to inhibit proliferation and induce apoptosis in several human tumor cells (7,8).…”
Section: Introductionmentioning
confidence: 99%